European drought management and perception - insights from 2018 & 2019 events - Blauhut, Veit (https://b2share.eudat.eu, 2021)
The data provides all data from the manuscript:"Lessons from the 2018-2019 European droughts: A collective need for unifying drought risk management " as submitted to AGu- Earth future. The hydro-climatic situations in 2018 and 2019 were described using a set of drought indices compiled by EDO for a variety of drought types including meteorological drought (Standardised Precipitation Index (SPI) for 1, 3, 6, 9 and 12 month accumulation periods), soil moisture drought (soil moisture anomaly; SM), hydrological drought (Low Flow Index; LFI, representing the discharge anomaly with respect to a daily threshold), and vegetation drought (anomaly of Fraction of Absorbed Photosynthetically Active Radiation; fAPAR). The SPI is given at a monthly resolution, whereas the other indices are presented in 10-day non-overlapping intervals. Detailed information on the drought indices can be found in the EDO indicator factsheets (https://edo.jrc.ec.europa.eu/edov2/php/index.php?id=1101). To increase comparability of the four indices, the EDO data was further classified into categorical drought classes according to the thresholds listed in Table 1. Furthermore, the fAPAR was restricted to the warm season in Europe from April to August and was not monitored for Iceland. In order to assess the country specific perception of drought, management and impacts with focus on the 2018 and 2019, a pan-European survey was designed by the International Association of Hydrological Science (IAHS) - Panta-Rhei “Drought in the Anthropocene” working group. National representatives of each country were selected and assigned responsibility to translate, distribute and evaluate the survey and all associated communication and feedback. The survey targeted representatives of water management organizations and water agencies. Survey respondents were selected by the national representatives aiming to provide a balanced view of national opinions and drought management practices (or actions), as well as local and regional knowledge within each country. The content of the survey was adapted from Teutschbein et al. (2019), who studied 290 Swedish municipalities to evaluate the relationship between perceived drought severity, impact, preparedness and management, aiming to compare stakeholder perception with hydrological drought indices. The perception of heat was not investigated. • The 26 questions of the survey covered the following themes: • Respondent background and water resource(s) used/managed, • General perception of drought and associated risks, • Drought risk-related concepts and the drought management applied, and • Perception of the 2018 and the 2019 drought events and their impacts